Effect of Political Factors on Tax Noncompliance Behaviour among Libyan Self-Employed Taxpayers - Abodher, Fareg Mustafa; Zainol Ariffin, Zaimah; Saad, Natrah (Allied Business Academies, 2018)
The current study attempts to empirically examine the effect of political affiliation and political instability on tax noncompliance behaviour among self-employed taxpayers of Libya. A self-administered questionnaire was distributed to the 498 Libyan self-employed. Total 312 questionnaires were fully completed that were used in the final data analysis. A structural equation modeling approach was employed using PLS-SEM 3.2.7. Results reveal that both political affiliation and political instability have a significant effect on tax noncompliance among self-employed Libyans.